Assessing predation parameters of predatory mite Typhlodromus bagdasarjani (Acari: Phytoseiidae) on different host plants - Afsoon Azadi-Qoort; Amin Sedaratian-Jahromi (Persian Journal of Acarology)
It is important to use standard parameters for assessing the biological performance of natural enemies in biological programs. The predation parameters of Typhlodromus bagdasarjani Wainstein & Arutunjan (Acari: Phytoseiidae) fed on the immature stages of the two-spotted spider mite, Tetranychus urticae Koch (Acari: Tetranychidae), reared on four different host plants including cucumber (cultivar ʻNeginʼ), tomato (cultivar ʻIsabellaʼ), eggplant (cultivar ʻBellʼ) and watermelon (cultivar ʻCrimsonʼ) were determined under laboratory conditions at 25 ± 1 ℃, 60 ± 5% R.H. and a photoperiod of 16:8 (L:D) h. Predation data were analyzed using the CONSUME MSChart. The lowest and highest estimated values for the net predation rate (C0) were recorded on eggplant (35.12 prey/individual) and tomato (95.87 prey/individual), respectively. The lowest transformation rate from prey population to predator offspring (Qp) (12.76 prey/egg) was recorded on cucumber which was not significantly different from those obtained on the others. The highest value for the stable predation rate (ψ) was recorded on the cucumber (2.49 prey/predator) and the lowest amount was recorded on the watermelon (1.93 prey/predator). The finite predation rate (ω) for T. bagdasarjani on the above-mentioned host plants was 2.73, 2.61, 2.03, and 2.04 (day−1), respectively. Our findings revealed the predation parameters of T. bagdasarjani fed on immature stages of T. urticae on four different host plants and will be helpful for its sustainable management in different agro-ecosystems.